Transfer Accuracy of Three Indirect Bonding Trays: An In Vitro Study with 3D Scanned Models - Hilal Gündoğ; Ayça Arman Özçırpıcı; Hande Pamukçu (Galenos Yayinevi, 2023)
Objective:The goal of the current study is to compare the transfer accuracy of two different conventional indirect bonding trays with 3D-printed trays.Methods:Twenty-two patients' upper dental models were duplicated, scanned and brackets were bonded digitally. Different indirect bonding trays (double vacuum formed, transparent silicone and 3D-printed) were prepared according to three groups. These trays were used for the transfer of the brackets to the patients' models, then models with brackets were scanned. GOM Inspect software was used for the superimposition of virtual bracket setups and models with brackets. A total of 788 brackets and tubes were analyzed. Transfer accuracies were determined according to the clinical limit of 0.5 mm for linear and 2° for angular measurements.Results:3D-printed trays had significantly lower linear deviation values than other trays for all planes (p<0.05). 3D-printed trays have significantly lower torque and tip deviation values than other groups (p<0.05). Transfer deviations were within the clinically acceptable limit for all transfer trays in horizontal, vertical and transverse planes. Deviation values of the molars were higher than those of the other tooth groups for all trays in the horizontal and vertical planes (p<0.05). Brackets were generally deviated toward the buccal direction in all tray groups.Conclusion:The transfer accuracy of 3D-printed transfer trays was more successful than the double vacuum formed and transparent silicone trays in the indirect bonding technique procedure. Deviations in the molar group were greater than those in the other tooth groups for all transfer trays.